Imaging of the Shoulder Bankart Lesion and its Variants - Leow, Kheng Song; Low, Soo Fin; Peh, Wilfred CG (Nepalese Journal of Radiology, 2019)
The glenoid labrum is an important soft tissue structure that provides stability to the shoulder joint. When the labrum is injured, affected patients may present with chronic shoulder instability and future recurrent dislocation. The Bankart lesion is the most common labral injury, and is often accompanied by a Hill-Sachs lesion of the humerus. Various imaging techniques are available for detection of the Bankart lesion and its variants, such as anterior labroligamentous periosteal sleeve avulsion and Perthes lesion. Direct magnetic resonance (MR) arthrography is currently the imaging modality of choice for evaluation of the various types of labral tears. As normal anatomical variants of glenoid labrum are not uncommonly encountered, familiarity with appearances of this potential pitfall helps avoid misdiagnosis.